Should I stay or should I go? The impact of a sense of control on young men's therapeutic engagement. Issue 3 (22nd May 2017) - Doherty, Matthew; Conway, Jane; Clark, Jane; Merritt, Frankie
Abstract: Background: Despite the fact that young men are difficult to engage in counselling, there is a paucity of research that examines the factors that may influence their decision making to enter, remain in or exit from therapy. One area that has remained particularly unrepresented in the literature is the role that a sense of control plays in this process. Aim/Methodology: Using a narrative approach, this study aimed to explore the stories of young men aged 18–25 and in doing so illuminated the impact of control on their counselling experiences. Findings: The study suggests that control impacts on young men's therapy‐related decision‐making in three distinct ways: making the decision to engage in therapy; controlling the process of therapy; and choosing who knows about the therapy. Implications: These emergent domains suggest that incorporating and discussing control with young male clients may provide the therapist with a means of increasing a young male's therapeutic engagement.